Crosstalk between hypoxia-inducible factor (HIF) and lncRNAs in digestive tumors: from molecular mechanisms to clinical translation - Gan, Lifeng; Luo, Peiyue; Zou, Junrong; Li, Wei; Chen, Qi; Cheng, Le; Zhang, Fangtao; Zhong, Haidong; Lu, Yiran; Zheng, Liying; Qian, Biao (Frontiers in Cell and Developmental Biology, 2025)
Hypoxia is a characteristic feature of the tumor microenvironment that significantly influences cancer progression and treatment responses. Hypoxia-inducible factor (HIF), a key regulator of hypoxic adaptation, has been demonstrated to modulate hypoxic gene expression profiles and signaling networks, thereby serving as a potential therapeutic target. Long-stranded non-coding RNAs (lncRNAs), defined as non-coding RNAs exceeding 200 nucleotides in length, regulate various cellular processes by modulating gene expression at transcriptional, post-transcriptional, and epigenetic levels. Evidence suggests that lncRNAs can be regulated by HIF at the transcriptional level. Conversely, HIF itself can be modulated by numerous lncRNAs, with alterations in these lncRNAs being associated with tumorigenesis, resulting in a reciprocal regulatory network. Recently, the critical role of lncRNAs in hypoxia-driven cancer progression has been elucidated in digestive tumors, including colorectal, pancreatic, gastric, and hepatocellular carcinomas. An increasing number of studies have revealed the complex interplay between lncRNAs and HIF in regulating various processes such as proliferation, metastasis, apoptosis, and drug resistance. In this paper, we aim to provide a comprehensive summary of recent advances regarding the roles of hypoxia and lncRNAs in digestive system tumors and to illustrate the mechanisms through which lncRNAs interact with hypoxia in tumor cells. This will enhance our understanding of the regulatory roles of lncRNAs in modulating the microenvironment of digestive system tumors, thereby facilitating the development of novel anticancer drugs.